2020
DOI: 10.2174/1876386302013010001
|View full text |Cite
|
Sign up to set email alerts
|

Couple Therapy Based on Mindfulness to Improve the Satisfaction of Life and Pain Self-Efficacy in Patients with Chronic Pain.

Abstract: Background: To manage chronic pain, in addition to medical interventions, several psychological treatments have been designed. In couple therapy based on mindfulness, in addition to the patients, their spouses, who care for the patients, were involved. The purpose of this research was to study the effectiveness of couple therapy based on mindfulness to improve life satisfaction and pain self-efficacy in patients with chronic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…These symptoms can lead to limit their ability to engage in normal activities such as attending school. The results of the current study agrees with A descriptive study done in Iran ,that was stated that no significant association was found between socio-demographic characterize of acute lymphoblastic leukemia children and their level of depression and anxiety (13) .…”
Section: Discussionsupporting
confidence: 90%
“…These symptoms can lead to limit their ability to engage in normal activities such as attending school. The results of the current study agrees with A descriptive study done in Iran ,that was stated that no significant association was found between socio-demographic characterize of acute lymphoblastic leukemia children and their level of depression and anxiety (13) .…”
Section: Discussionsupporting
confidence: 90%
“…Respondents rate each item on a 5-point scale, ranging from 0 (not at all) to 4 (all the time), with higher scores indicating greater levels of pain catastrophizing. The PCS's validity and reliability have been confirmed through numerous studies across different populations and settings (Firoozi et al, 2018). I E-ISSN: 3041-8542…”
Section: Pain Catastrophizingmentioning
confidence: 88%
“…In these patients, pain often remains despite the improvement of inflammation and may even gradually increase (10). Meanwhile, pain acceptance is not about ignoring pain or increasing behavioral activity to control pain, but rather a behavioral change that entails better daily functioning despite the presence of pain (11). According to research, pain acceptance leads to increased resilience and quality of life for patients (12,13).…”
Section: Introductionmentioning
confidence: 99%